2019
DOI: 10.3390/v11020144
|View full text |Cite
|
Sign up to set email alerts
|

Human Sapovirus among Outpatients with Acute Gastroenteritis in Spain: A One-Year Study

Abstract: Viral agents of human gastroenteritis affect people of all ages across the globe. As a mainly self-limiting disease, it is difficult to evaluate the real prevalence of etiological agents circulating in each region. Many of the analyzed outbreaks are caused by viruses of the family Caliciviridae, especially the genus Norovirus (NoV). Most studies have focused on other enteric viruses, leaving sapovirus (SaV) underestimated as an important emerging human threat. This one-year study analyzed clinical samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 31 publications
9
39
2
Order By: Relevance
“…The overall SaV-positive rate reported in the present study during the period 2010 to 2018 (1.6%, ranged from 0 to 2.8%) is more or less the same as other similar studies including Bangladesh (2.7%) (Dey et al, 2007), China (1.9%) (Ren et al, 2013), Vietnam (1.4%) (Trang et al, 2012), and Thailand (1.2 and 1.9%) (Khamrin et al, 2017;Supadej et al, 2019). However, when compared to the studies conducted in different geographical regions, the prevalence of SaV detected in this study was lower than those reported from Japan (4.8%), Philippines (7%), USA (5.4%), Italy (6%), Denmark (8.8%), Finland (9.3%), Spain (15.6%), and Nicaragua (17%) (Biscaro et al, 2018;Bucardo et al, 2014;Chhabra et al, 2013;Oka et al, 2015;Thongprachum et al, 2015;Varela et al, 2019). The variation of SaV prevalence in different studies could be explained, at least in part, by the difference in study locations, the detection methods, and the emergence of new epidemic strains.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The overall SaV-positive rate reported in the present study during the period 2010 to 2018 (1.6%, ranged from 0 to 2.8%) is more or less the same as other similar studies including Bangladesh (2.7%) (Dey et al, 2007), China (1.9%) (Ren et al, 2013), Vietnam (1.4%) (Trang et al, 2012), and Thailand (1.2 and 1.9%) (Khamrin et al, 2017;Supadej et al, 2019). However, when compared to the studies conducted in different geographical regions, the prevalence of SaV detected in this study was lower than those reported from Japan (4.8%), Philippines (7%), USA (5.4%), Italy (6%), Denmark (8.8%), Finland (9.3%), Spain (15.6%), and Nicaragua (17%) (Biscaro et al, 2018;Bucardo et al, 2014;Chhabra et al, 2013;Oka et al, 2015;Thongprachum et al, 2015;Varela et al, 2019). The variation of SaV prevalence in different studies could be explained, at least in part, by the difference in study locations, the detection methods, and the emergence of new epidemic strains.…”
Section: Discussioncontrasting
confidence: 79%
“…Enteric caliciviruses including noroviruses and sapoviruses are the major causes of AGE of human in all age group worldwide (Khamrin et al, 2017;Lu et al, 2014;Neo et al, 2017;Sala et al, 2014). The detection rate of SaV infection in many countries around the world have been reported with a range from 0.2 to 39% in children and 2.2 to 15.6% in all age groups (Magwalivha et al, 2018;Oka et al, 2015;Varela et al, 2019). In Thailand, the prevalence of SaV was detected between 0% and 15.0% (Kumthip & Khamrin, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, high rates of SaV infections more than 10% were reported in Latin America and Spain. 35 For example, SaV could be detected in 17.3% (57 of 330) of diarrheic children in Nicaragua between 2009 and 2010. 31 In Brazil, 18.6% of fecal samples and 36.3% of nasopharyngeal swab samples were detected SaV-positive from 102 hospitalized children with symptoms of acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, only six (0.7%) samples were detected SaV‐positive out of 889 fecal specimens from 2012 to 2014 . However, high rates of SaV infections more than 10% were reported in Latin America and Spain . For example, SaV could be detected in 17.3% (57 of 330) of diarrheic children in Nicaragua between 2009 and 2010 .…”
Section: Discussionmentioning
confidence: 99%